Arabic Language Teaching Practices in a Culturally Embedded Context: The Case of Bayan Indigenous Village in Lombok - Binti Syufiana Budairoh; Yusraini Yusraini; Irfan Irfan; Muhammad Qodri; Mustar Mustar; Mohamad Hussin (An Nabighoh Jurnal Pendidikan Dan Pembelajaran Bahasa Arab, 2026)
Background: As the language used in the Quran and the Hadith, Arabic holds a crucial position in Islamic education. The success of Arabic language learning is determined by selecting Arabic language teaching methods that are appropriate to the students’ sociocultural context. Therefore, understanding the Arabic language teaching methods used at the madrasah tsanawiyyah in the traditional village of Bayan and their relevance to the local culture is of considerable importance. Research Objectives: This study aims to analyze the Arabic language teaching methods used at a madrasah located in the traditional village of Bayan and to examine the contextual factors that influence their implementation. Methodology: This study employed a descriptive qualitative approach with teachers and learners as the research subjects. Semi-structured interviews, observations, and documentation were used to collect data. The research instruments included interview guidelines and observation sheets. The data were analyzed using the Miles and Huberman model, and data validity was assessed through triangulation. Results: The research findings indicate that the sam’iyyah wa syafahiyyah (audiolingual/audio-oral) method was used, even though the teacher claimed to be using the mubasyarah (direct) method. This is evident in the learning process, which focuses on repetition and dialogue. In addition, the limited facilities and infrastructure resulted in a lack of variety in the teaching methods employed. Unique Contribution: This study contributes to the literature by providing an empirical description of Arabic language teaching practices at a madrasah located within an indigenous community and highlighting the role of local sociocultural conditions in shaping teaching adaptations. Conclusion: The implementation of the audiolingual method in the study conducted at the madrasah was shaped primarily by pedagogical practices and institutional conditions. Although the sociocultural context of the traditional village of Bayan did not directly determine the teaching methods used, it did influence the adaptation of learning objectives and priorities. Therefore, efforts to improve Arabic language learning in indigenous communities must combine pedagogical development with sensitivity to local sociocultural conditions. Recommendations: Enhancing teachers’ pedagogical competencies through regular professional development is necessary. In addition, various teaching methods that integrate listening, speaking, reading, and writing should be balanced and supported by adequate learning resources.